Nutrient sensing and TOR signaling in yeast and mammals. (17th January 2017) - González, Asier; Hall, Michael N
Abstract: Coordinating cell growth with nutrient availability is critical for cell survival. The evolutionarily conserved TOR (target of rapamycin) controls cell growth in response to nutrients, in particular amino acids. As a central controller of cell growth, mTOR (mammalian TOR) is implicated in several disorders, including cancer, obesity, and diabetes. Here, we review how nutrient availability is sensed and transduced to TOR in budding yeast and mammals. A better understanding of how nutrient availability is transduced to TOR may allow novel strategies in the treatment for mTOR‐related diseases. Abstract : As part of our metabolism focus, this review summarizes how nutrient availability is recognized and integrated by the conserved TOR cell growth regulator.